INNOVATION AND INVESTMENT AS A FACTOR OF PROVIDING COMPETITIVE ABILITY OF THE NATIONAL ECONOMY AND THE TRANSFORMATION OF ECONOMIC RELATIONS - Avedian L.Y. (Pressing Problems of Public Administration, 2016)
The problems associated with the de nition of the role of investment and innovation as a key factor inensuring the competitiveness of the national economy. Analyzes the obstacles to the transformationof economic relations and possible ways to address them.